Role of α/β hydroxylase domain containing protein 2 in stallion sperm activation - McQuagge, Matthew, author; Bruemmer, Jason, advisor; Pinedo, Pablo, committee member; Graham, James, committee member; Winger, Quinton, committee member (Colorado State University. Libraries, 2019)
Cell signaling pathways involved in stallion sperm activation are not completely understood. Furthermore, failure of equine in vitro fertilization is commonly attributed to an inability to successfully capacitate sperm. Sperm activation describes the process by which sperm undergo capacitation, hyperactivation, and acrosome reaction in preparation for interaction with an oocyte. 2-arachidonoylglycerol (2AG) is found in the human sperm membrane and prevents calcium influx through the CatSper channel. The α/β hydroxylase domain containing protein 2 (ABHD2) is also found in the human sperm membrane and functions as a progesterone receptor. When progesterone binds to ABHD2, it removes 2AG from the membrane allowing CatSper to open, which leads to calcium entrance into the cell, resulting in sperm activation. It is unclear if this mechanism holds true in stallion. Experiments were conducted to test the hypothesis that progesterone causes sperm activation through interaction with ABHD2 by 1) determining whether the ABHD2 receptor exists on stallion spermatozoa, 2) determining if progesterone binds to ABHD2 on stallion spermatozoa and 3) demonstrating the role of ABHD2 in sperm activation through correlations between ABHD2 and hyperactivation and/or acrosome reaction. Immunoblotting identified ABHD2 protein in stallion sperm and immunocytochemistry (ICC) localized the receptor to the tail region of stallion spermatozoa. Immunocytochemistry also demonstrated that ABHD2 binds progesterone by restricting fluorescence exhibited by ABHD2 when incubated with progesterone. Stallion sperm were evaluated for hyperactivation with computer assisted sperm analysis (CASA) following incubation in capacitation medium with either 1) an endogenous activator of sperm; 3 µM progesterone (P4), 2) a positive pharmacological stimulator of hyperactivation not associated with ABHD2; procaine or 3) a known ABHD2-action inhibitor methyl arachidonyl flourophosphatnate (MAFP). MAFP is a serine hydroxylase inhibitor and functions by preventing the removal of 2AG caused by exposure of ABHD2 to progesterone and, thus, limits hyperactivation. Flow cytometry was used to measure the acrosomal status of treated sperm as a subset of the hyperactivation measurements. When MAFP was administered prior to treatment with either P4 and/or procaine the hyperactive movement was inhibited (p < 0.05) in the presence of P4 but did not affect procaine induced activity. Results were similar for all ejaculates. The reduced hyperactivation of sperm when incubated with both progesterone and MAFP illustrates a potential connection between ABHD2 and CatSper. No change in acrosomal status was discovered through incubation with P4, procaine, or MAFP. These results indicate 1) that ABHD2 is present on stallion sperm, 2) that progesterone binds to ABHD2 and 3) that progesterone has the potential for causing hyperactivation but does not affect the acrosome reaction.